All In One Civil Engineering PE Exam Guide: Highway Geometric Design - Parabolic Curves - Goswami, Indranil (McGraw-Hill's AccessEngineering., 2015)
This video demonstrates the calculation of geometric parameters of a parabolic vertical curve.